Association between Angiotensin-Converting Enzyme Inhibitors and Troponin in Acute Coronary Syndrome - Minuzzo,Luiz (2014)
Background:Cardiovascular disease is the leading cause of mortality in the western world and its treatment should be optimized to decrease severe adverse events.Objective:To determine the effect of previous use of angiotensin-converting enzyme inhibitors on cardiac troponin I measurement in patients with acute coronary syndrome without ST-segment elevation and evaluate clinical outcomes at 180 days.Methods:Prospective, observational study, carried out in a tertiary center, in patients with acute coronary syndrome without ST-segment elevation. Clinical, electrocardiographic and laboratory variables were analyzed, with emphasis on previous use of angiotensin-converting enzyme inhibitors and cardiac troponin I. The Pearson chi-square tests (Pereira) or Fisher's exact test (Armitage) were used, as well as the non-parametric Mann-Whitney's test. Variables with significance levels of <10% were submitted to multiple logistic regression model.Results:A total of 457 patients with a mean age of 62.1 years, of whom 63.7% were males, were included. Risk factors such as hypertension (85.3%) and dyslipidemia (75.9%) were the most prevalent, with 35% of diabetics. In the evaluation of events at 180 days, there were 28 deaths (6.2%). The statistical analysis showed that the variables that interfered with troponin elevation (> 0.5 ng / mL) were high blood glucose at admission (p = 0.0034) and ST-segment depression ≥ 0.5 mm in one or more leads (p = 0.0016). The use of angiotensin-converting inhibitors prior to hospitalization was associated with troponin ≤ 0.5 ng / mL (p = 0.0482). The C-statistics for this model was 0.77.Conclusion:This study showed a correlation between prior use of angiotensin-converting enzyme inhibitors and reduction in the myocardial necrosis marker troponin I in patients admitted for acute coronary syndrome without ST-segment elevation. However, there are no data available yet to state that this reduction could lead to fewer severe clinical events such as death and re-infarction at 180 days.